Effect of soil interaction on the performance of liquid column dampers for seismic applications. - Ghosh, Aparna (Earthquake engineering & structural dynamics.)
The effects of soil structure interaction (SSI) while designing the liquid column damper (LCD) for seismic vibration control of structures have been presented in this study. The formulation for the input-output relation of a flexible base structure with attached LCD has been presented. The superstructure has been modelled by a single degree of freedom (SDOF) system. The non-linearity in the orifice damping of the LCD has been replaced by equivalent linear viscous damping by using equivalent linearization technique. The force deformation relationships and damping characteristics of the foundation have been described by complex valued impedance functions. Through a numerical stochastic study in the frequency domain, the various aspects of SSI on the functioning of the LCD have been illustrated. A simpler approach for studying the LCD performance considering the SSI, using an equivalent SDOF model for the soil structure system available in literature by Wolf has also been presented.